The Effect of O Organizational Culture, Work Discipline, and Communication Competency, on Employee Performance in the Regional Financial Management Agency of Tambrauw Regency, West Papua Province - Didymus Wabia; David PE Saerang; Rita N. Taroreh (Research Parks Publishers, 2021)
Test the validity of the research instrument, the results obtained that all instrument items are valid. This is evidenced by the probability value (sig) for each question item is less than 0.05. Thus, all questionnaire items can be continued for reliability testing. The reliability test of all instrument items has a Cronbach Alpha value above 0.6. This means that all items are reliable. Thus the whole question (questionnaire) can be used for research. The results of the multicollinearity test for all variables do not have a tolerance value less than 0.10 and none have a VIF value greater than 10. Thus, the regression model in this equation is free from multicollinearity. Normality test shows the points are around the diagonal line. It is interpreted that the regression model has normally distributed data. The heteroscedasticity test showed no symptoms of heteroscedasticity because the dots spread randomly and did not show a certain pattern. The results of the analysis, the Organizational Culture variable (X1) has a tcount value of 0.59` with a probability of 0.558. Because the probability value (sig) t > 5% (0.558 > 0.05) then partially the Organizational Culture variable (X1) has no significant effect on the Employee Performance variable (Y) if the other independent variables remain in value. Thus, the hypothesis which states that there is a positive and significant effect of the Organizational Culture variable (X1) on the Employee Performance variable (Y) is rejected. Based on the results of the analysis, the Work Discipline Variable (X2) has a tcount value of 2. 818 with a probability of 0.008. Because the probability value (sig) t < 5% (0.008 <0.05), partially the Work Discipline variable (X2) has a significant positive effect on the Employee Performance variable (Y) if the other independent variables remain in value. Thus the hypothesis which states that there is a positive and significant influence on the Work Discipline variable (X2) on the Employee Performance variable (Y) is accepted. Based on the results of the analysis, the Communication Competency Variable (X3) has a tcount of 2,649. with a probability of 0.012. Because the probability value (sig) t < 5% (0.012 <0.05) then partially the Communication Competence variable (X3) has a significant effect on the Employee Performance variable (Y) if the other independent variables remain in value.